The role of educational technology in improving the level of academic achievement of science and techniques of physical activities and sports - kacir abderezak, (sports creativity, 2025)
This study aims to address the role of educational technology in improving the level of academic achievement of students of science and techniques of physical activities and sports, and the extent to which we keep pace with developments in all fields, the descriptive method was used, the sample of the study included 30 students from the research community of 147 students from the Department of Science and techniques of physical activities In order to reach more accurate, objective and identical results, we selected a random sample. One of the most important tools used was the questionnaire. The study reached a number ofconclusions. Educational data and teaching aids learning have an important role in improving the academic achievement level, with the need to support the educational process by providing appropriate means of curricula